Ascenção homem - máquina: a ascensão da inteligência artificial e suas implicações éticas - ASCENÇÃO, Graciângela de Jesus Abreu (2024)
The main aim of this philosophical dissertation is to investigate the rise of artificial intelligence (AI) and its potential to change and reshape relationships between humans, as well as between humans and technology, deepening and generating ethical challenges. This disruptive technology is present in almost every area of life, transforming everyday practices and challenging existing ethical norms in society. The roots of artificial intelligence (AI) go back to antiquity, when philosophers speculated about thinking machines. Myths and narratives in books and films reflect the human quest to understand and replicate intelligence, broadening our perception of this technology. This work explores the evolution of AI, from its philosophical origins to its contemporary applications, highlighting the influence of philosophers such as René Descartes, Alan Turing, Mark Coeckelbergh and Luciano Floridi. The objectives of this research are: 1) To examine the historical evolution of AI and its applications, identifying how these technologies transform social interactions and decision-making; 2) To analyse AI as an ethical object; 3) To investigate the ethical implications of AI by addressing issues such as privacy, algorithmic bias and human interaction with artificial agents. The central problem of the dissertation revolves around the ethical implications of this technology and how it influences our lives. The study reveals that AI, far from being a neutral tool, carries values and prejudices that can perpetuate social inequalities. The indiscriminate use of AI in important decisions demonstrates the risks of over-reliance on this technology. In addition, the growing integration of AI into human interactions raises questions about the authenticity of these relationships. The methodology involves a qualitative approach, using a literature review, analysing books and philosophical articles as well as relevant case studies. At a time when technology is advancing rapidly, it is imperative to reflect: how far are we willing to allow AI to mould our lives? The paper concludes that while AI presents significant opportunities, it is crucial to develop robust ethics to mitigate its risks and ensure that its use benefits everyone.